Budget Impact Analysis of Risk-Stratified Prostate Cancer Screening in the UK using National Audit Data - Fitzjohn, Jean-Pierre; Bolodeoku, John; Chinegwundoh, Frank; Rogers, Jeremy; Chambers, Kadifa; Anyaeche, Chidi; Odeyemi, Isaac (British Journal of Healthcare and Medical Research, 2026)
Objective: This study performs a budget impact analysis of a hypothetical risk-stratified prostate cancer (PCa) detection programme in the UK. To contextualise this economic case, the profound ethnic and socioeconomic disparities in care are identified in the latest National Prostate Cancer Audit (NPCA) data. Methods: A budget impact analysis was conducted from a UK National Health Service (NHS) perspective over a one-year period. A cohort representing the 55,241 men diagnosed with PCa in England in 2023 was modelled, with baseline stage distribution (TNM) sourced from the NPCA 2024 Report(National Prostate Cancer Audit, 2025a). First-year, stage-specific mean treatment costs (2017/18 GBP) were derived from a published UK health economic study. We quantified the net budget impact of a hypothetical 10% stage-shift from Stages T2, T3, and T4 to Stage T1 (Wills et al., 2023). Results: The NPCA data revealed for men with high-risk disease, Black men were substantially less likely to receive curative radical treatment than White men (67.8% vs. 81.6% for ages 60-69) (National Prostate Cancer Audit, 2025a). Our model projected that a 10% stage shift had a net initial cost saving of £1.72 million for this annual cohort. The long-term economic benefit overshadows this short-term saving. The model averted 331 metastatic cases, each associated with an estimated one-year NHS cost of £63,284–£216,118 (see Appendix C). Conclusion: A risk-stratified PCa detection strategy in the UK offers a rare "dual dividend": it provides a direct mechanism to address profound health inequities while simultaneously being projected to be cost-saving to the NHS, both immediately and in the long term. These findings provide a robust economic and ethical mandate for the UK National Screening Committee to recommend the implementation of such a strategy.